الأمن القانوني في النظام القانوني السوداني تطبيقا على قانون تفكيك نظام الثلاثين من يونيو 1989 م. وإزالة التمكين للعام 2019 م. - عبدالغفار، إيهاب عبدالحميد عبدالعال (مركز بحوث ودراسات دول حوض البحرالأحمر وجامعة البليدة2, 2024)
هدف المقال إلى إبراز فكرة الأمن القانوني ومقوماته في الدولة على أساس الضمان في حفظ حقوق الأفراد الدستورية، كما تطرق إلى الممارسات الدستورية والعملية في بعض دساتير بعض الدول لإظهار مقومات الأمن القانوني وتسليط ذلك على التجربة الدستورية السودانية مؤخرا، وقد استخدمت الدراسة منهجية علمية تكونت من المنهج الوصفي من خلال المعلومات التي توفرت لنا والمنهج التاريخي باسترجاع بعض التجارب الدستورية السودانية. وتوصلت النتائج إلى أن فكرة الأمن القانوني في الدساتير السودانية تتأثر سلبا وإيجابا بالنخب السياسية الحاكمة وعجزها في التوفيق بين مصالحها ومصالح الشعب. وأوصت الدراسة بمراعاة مقومات الأمن القانوني في الدستور الدائم المقترح والبعد عن المصالح الحزبية الضيقة. The article aimed to highlighting the idea of legal security and its components in the state on a basis of guaranteeing the preservation of individual’s constitutional rights, we also discuss the constitutional and practical practices in some constitutions of some countries to demonstrate the elements of legal security and shed light on the recent Sudanese constitutional experience. The study used a scientific methodology consisting of the descriptive approach based on the information available to us and a historical approach by recalling some Sudanese experiences. The results concluded that the idea of legal security in Sudanese constitutions is affected both positively and negatively by the ruling political elites and their inability to reconcile their interests with the interests of the people. The study recommended taking into account the components of legal security in the proposed permanent constitution and staying away from narrow partisan interests.
Keywords: القضاء السوداني -- الأمن القانوني -- الحقوق الدستورية -- الأسس الدستورية